OCENA SKUTECZNOŚCI OPERACJI POKOJOWEJ ONZ W BYŁEJ JUGOSŁAWII - Ocieczek, Bolesław (Wydział Prawa i Administracji UAM, 1998)
The conflict in former Yugoslavia is in connexion with process of creation of new political order in Europe and in the world after the so-called cold war ended in 1989. Initial approach to the problem, considered in the beginning as intra-European, was characterised by the will not to impose solution from the outside and to respect political aspirations of the peoples within the framework o f loose confederation. Lack o f political uniformity in Europe has led however quickly to a modification of this formula in favour of creating independent States of national expression. This new formula was positively verified in case of ethnically formed countries but it proved to be tragic for multinational Bosnia. The Author discusses among others a genesis o f the conflict, a beginning of disintegration of Yugoslavia, the outbreak of war and instruments of peaceful operations applied for to suppress the conflict. The Author analyses critically standpoints of particular States in this generation and activities of the UN troops hitherto operated.
EVALUATION OF EFFECTIVENESS OF PEACE MAKING OPERATION OF THE UNITED NATIONS IN FORMER YUGOSLAVIA